E-tailing quality index - Pankaj Rawal; Deepali Singh (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
This research study aims at developing and validating E-tailing quality index. It consists of the literature reviews of the past researches, which were done by various authors and while finding the dimensions for the e-tailing quality. The scale development methodology results into six factors comprises of Platform accommodation and customer centric functions, Satisfactory Product/Service quality, Knowledge about product and promptness, Delivery and Sales support, Customer service, Vision and Mission. It is a strategic tool to implement e-tailing quality index effectively and efficiently. This research can also be used to find the opportunities and critical areas which require attention.
Keywords: 650; E-tailing; Retailing; Marketing; Quality Index